2018
DOI: 10.7567/jjap.57.04fg09
|View full text |Cite
|
Sign up to set email alerts
|

5.0 kV breakdown-voltage vertical GaN p–n junction diodes

Abstract: A high breakdown voltage of 5.0 kV has been achieved for the first time in vertical GaN p-n junction diodes by using our newly developed guardring structures. A resistance device was inserted between the main diode portion and the guard-ring portion in a ring-shaped p-n diode to generate a voltage drop over the resistance device by leakage current flowing through the guard-ring portion under negatively biased conditions before breakdown. The voltage at the outer mesa edge of the guard-ring portion, where the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 30 publications
1
58
0
Order By: Relevance
“…This result corroborates the ability of AZ400K to mitigate ICP-induced etch damage [11]. However, the etched-and-regrown diode electrical performance significantly lags that of continuously-grown GaN diodes [2][3][4][5][6], which could be due to substrate effects, lack of JTE, Si incorporation during regrowth, or combinations thereof. While etched-and-regrown GaN diode performance lagged that of continuously-grown GaN diodes, they greatly exceeded the Si unipolar limit.…”
Section: Fig 3 Reverse I-v Data For Etched-and-regrown Diodes and Plsupporting
confidence: 73%
See 1 more Smart Citation
“…This result corroborates the ability of AZ400K to mitigate ICP-induced etch damage [11]. However, the etched-and-regrown diode electrical performance significantly lags that of continuously-grown GaN diodes [2][3][4][5][6], which could be due to substrate effects, lack of JTE, Si incorporation during regrowth, or combinations thereof. While etched-and-regrown GaN diode performance lagged that of continuously-grown GaN diodes, they greatly exceeded the Si unipolar limit.…”
Section: Fig 3 Reverse I-v Data For Etched-and-regrown Diodes and Plsupporting
confidence: 73%
“…The rapid development of GaN substrates has stoked interest in GaN power diodes [2][3][4][5][6] because of their potential to outperform SiC devices owing to the higher μ and larger E crit for GaN. Moving GaN beyond diodes to merged p-i-n Schottky (MPS) devices or junction field-effect transistors (JFETs) will require selective area p-type doping, but this has been difficult to achieve.…”
mentioning
confidence: 99%
“…In addition to having a low dislocation density, growing GaN devices on GaN substrates (GaN-on-GaN) allows vertical device architectures which have better thermal management, higher reliability, and high breakdown voltages using small devices as compared to lateral devices [10]. Recent research on high-power vertical devices on bulk GaN can be found in references [11,12,13,14,15,16]. It has also been shown that GaN-on-GaN LEDs can operate efficiently at high current density unlike heteroepitaxial LEDs which experience a strong efficiency droop as current density is increased [17].…”
Section: Introductionmentioning
confidence: 99%
“…Free‐standing GaN substrates allow epitaxial growth of a thick drift layer with low dislocation density. Compared with a p–n diode, a Schottky diode has the advantage of a lower turn‐on voltage . The key issue is to form thick, high‐quality n‐GaN layers with low carrier density for the drift layer.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with a p-n diode, a Schottky diode has the advantage of a lower turn-on voltage. [11][12][13][14][15][16] The key issue is to form thick, high-quality n-GaN layers with low carrier density for the drift layer.…”
Section: Introductionmentioning
confidence: 99%